Interoperability among healthcare organizations acting as certification authorities. - Bourka, A.
One of the main problems in public key infrastructures (PKI) is currently the lack of interoperability at international level, which is greatly dependent on the automation of the cross-certification procedure using certificate policies (CP). This paper addresses the aforementioned need by presenting a method for the automated development and comparison of CPs, with main emphasis on healthcare environments. The basic elements of this method include standardization of the CP content for healthcare, a prototype decision-making algorithm for CPs comparison, representation of CPs in extensible markup language, as well as a JAVA-based CP comparison tool. The final aim of the paper is to contribute toward the technical implementation of an on-line automated cross-certification service, yielding PKI interoperability and promoting information exchange between healthcare establishments.
Keywords: JAVA-based CP comparison tool; Certification authorities; Cross-certification procedure; Decision-making algorithm; Extensible markup language; Healthcare organizations; Public key infrastructures